Republic of Montenegro : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
Euroization has served Montenegro well by anchoring inflation expectations, and shifted the burden of adjustment to fiscal and structural policies. The paper looks at trends and how developments in the tourism industry have contributed to the shaping of the economy. The lack of monetary and exchange rate policies in Montenegro puts a premium on a well-designed and appropriate fiscal policy. This paper has presented a dynamic analysis of the structure of the banking sector of Central and Eastern European countries.